Identification of hit compounds for squalene synthase: Three‐dimensional quantitative structure‐activity relationship pharmacophore modeling, virtual screening, molecular docking, binding free energy calculation, and molecular dynamic simulation. (23rd August 2017) - Hou, M.; Yan, G.; Ma, X.; Luo, J.; Hou, X.; Zhou, M.; Pu, C.; Han, X.; Zhang, W.; Zhang, M.; Shi, J.; Li, R.
Abstract : Squalene synthase (SQS) is the key precursor in the synthesis of cholesterol. Located downstream in relation to hydroxy methylglutaryl coenzyme A reductase and having no influence on the formation of biologically necessary isoprenoids make it an interesting target for the development of cholesterol lowering drugs with fewer side effects. To discover novel SQS inhibitors, three‐dimensional quantitative structure‐activity relationship pharmacophore models were built and further validated by cost function analysis, test set validation, and decoy set validation to obtain a reliable model for virtual screening against a database that contains 5.5 million compounds. The interactions between SQS and the ligands were predicted by an integrated protocol that contains molecular docking, molecular mechanics/generalized born surface area, and molecular dynamic simulation. After that, five compounds with best binding affinities and binding modes were obtained as potential hits for further study and three of them showed inhibitory effects against SQS. Abstract : To find new squalene synthase inhibitors, pharmacophore‐based virtual screening, molecular docking, binding free energy calculation, and molecular dynamics were used. As a result, 3 of the 5 hits showed inhibitory activity.